Recent research on flexible fixtures for manufacturing processes - Bakker, Otto Jan; Papastathis, Thomas; Ratchev, Svetan; Popov, Atanas A. (Open Access Plus, 2013)
Fixtures, are used to fixate, position and support workpieces, and form a crucial tool in manufacturing. Their performance influences the manufacturing (and assembly) process of a product. Furthermore, fixturing can form a significant portion of the needed investment and total process planning time for the manufacturing system. Many fixturing concepts, as contribution to increase the flexibility of the manufacturing system, are reported in the literature. The flexible fixturing designs can be classified into the following seven categories: modular fixtures, flexible pallet systems, sensor-based fixture design, phase-change based concepts, chuck-based concepts, pin-type array fixtures and automatically reconfigurable fixtures. It is observed that the more intelligent and automated fixturing systems are designed with the demands for automation in certain industries in mind. Furthermore, different fixturing solutions suit the engineering demands for different manufacturing areas, this means that for the foreseeable future all technologies will remain current. From the self-reconfigurable fixturing techniques a new fixturing capability is emerging: in process reconfigurability for the optimal placement of clamps and supports during the whole process time. These several concepts together with some recent patents are studied here. The paper concludes with some prospective research directions in the field of flexible fixturing.